Tingkat Kejadian Carpal Tunnel Syndrome pada Penjual Rujak di Lokasi Wisata Pulau Ambon Tahun 2023 - Krista, Imanuela (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2025)
Introduction: Rujak is one of the famous traditional culinary delights. In the activity of kneading rujak, sellers use more wrist movements which can increase a risk of carpal tunnel syndrome (CTS) which is a symptom that arises due to repeated movements over a long period of time, causing stress on the median nerve that passes through the carpal tunnel. Aim: The prevalence of CTS in rujak sellers is not yet known with certainty, therefore the author conducted this research to determine the prevalence of carpal tunnel syndrome in rujak sellers at coastal tourist locations on Ambon Island in 2023. Methods: This research was held at Natsepa beach and Tapal Kuda beach in September 2023. This research is a descriptive study with data sources coming from primary data using a cross-sectional approach and using a total sampling method. Data collection was carried out by interacting directly with respondents in the process of filling out the Boston Carpal Tunnel Syndrome Questionnaire. Results: From the 43 samples of rujak sellers who were the subjects of this study, the results showed that the prevalence of carpal tunnel syndrome was 74% in rujak sellers and the highest prevalence in the age range 45-59 years, normal body mass index, 18 years of work and 40 hours work duration. Discussion: The prevalence of carpal tunnel syndrome in rujak sellers who have CTS is influenced by repetitive movements accompanied by other risk factors (age, body mass index, duration and length of work) Keywords: Carpal tunnel syndrome, Prevalence of CTS, Rujak seller.